Final Contributions to the Problems and Methods of Psychoanalysis. - Ferenczi, Sándor, 1873-1933 (Karnac classics., 1994)
This final volume includes "Confusion of Tongues Between Children and Adults" in which Ferenczi formulates his controversal ideas on childhood sexuality, and the conflict between the languages of tenderness and passion. First published in 1955, this book contains papers written by Ferenczi during his last years and some of his unpublished notes. It demonstrates Ferenczi's combination of great clinical understanding and an almost uncanny insight into unconscious process. Among the forty important items included are papers on the following: "Freud's Influence on Medicine", "Laughter", "Epileptic Fits", "Dirigible Dreams", "Philosophy and Psycho-Analysis", "Paranoia", "The Interpretation of Tunes Which Come into One's Head" and "The Genesis of Jus Primae Noctis".